Private Sector Participation and the Development of University Education in the Nigeria’s Fourth Republic, 1999-2021: A Historical Analysis - ADESOTE Samson Adesola (International Journal of Educational Review, 2024)
The main thrust of this paper is to historicize the involvement of the private sector in the development of university education in Nigeria in the Fourth Republic. While the year 1999, marked the commencement of the birth of the second batch of private universities in Nigeria, the year 2021 was when the last batch of private universities were granted provisional licenses of operation by the Federal Government. History of educational development in Nigeria has its origin in the activities of the private sectors, that is, the Christian missions. Their involvement in the development of western education in the country between the late 19th and 20th centuries was mainly confined to the provision of primary and secondary education. Up to the birth of the Fourth Republic in 1999, the provision of university education in the country was exclusively the responsibility of both the Federal and the State governments. Although an attempt was made during the Second Republic, 1979-1983, to encourage private sector participation, this eventually failed. However, with the return to civil rule in 1999, the country witnessed the emergence of the second attempt towards private sector involvement in the development of university education. The paper argues that the active involvement of the non-state actors in the delivery of university education in Nigeria since 1999 has helped in improving efficiency in delivery, expanding service coverage as well as increasing manpower production. The methodology adopted for this work is historical, qualitative and quantitative, utilizing materials from both primary and secondary sources.